# |
ODE |
Mathematica |
Maple |
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (-2-i\right ) x y^{\prime }+3 i y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 \pi y = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x^{2}+x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }+x^{6} y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 y^{\prime }+3 x^{2} y = 0
\] |
✓ |
✗ |
|
\[
{}x y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+x -2\right )^{2} y^{\prime \prime }+3 \left (x +2\right ) y^{\prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+\left (4 x^{4}-5 x \right ) y^{\prime }+\left (x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (-3 x^{2}+x \right ) y^{\prime }+y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }+5 x y^{\prime }+3 x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x \,{\mathrm e}^{x} y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+\left (x^{2}+5 x \right ) y^{\prime }+\left (x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-4 x \,{\mathrm e}^{x} y^{\prime }+3 y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (-x^{2}+1\right ) y^{\prime \prime }+3 \left (x^{2}+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x^{2} y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+\left (-x^{3}+3\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+2 \left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x^{2} y^{\prime }+\left (4 x -2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}+x}{y-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{x -y}}{1+{\mathrm e}^{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} y^{2}-4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y}{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{x y+x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}+x y+x^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y+x \,{\mathrm e}^{-\frac {2 y}{x}}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x -y+2}{x +y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x +3 y+1}{x -2 y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+1}{2 x +2 y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x +y-1\right )^{2}}{2 \left (x +2\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x y+\left (x^{2}+3 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+x y+\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+{\mathrm e}^{y} \left (1+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )^{2}-\sin \left (x \right ) \sin \left (2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{3}-x^{3} y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+\left (x -y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y \,{\mathrm e}^{2 x}+2 x \cos \left (y\right )+\left ({\mathrm e}^{2 x}-x^{2} \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 \ln \left (x \right ) x^{2}+x^{2}+y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{3}+2+3 y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )-2 \sin \left (x \right ) \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{2} x^{3}+2 y+\left (3 x^{4} y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y}+x \,{\mathrm e}^{y}+x \,{\mathrm e}^{y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{\mathrm e}^{x} y^{\prime } = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+4 {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+k^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-2 y^{\prime } = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -\frac {1}{2 {y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\sin \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\sin \left (y\right ) = 0
\] |
✗ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (x \right ) = y_{1} \left (x \right ), y_{2}^{\prime }\left (x \right ) = y_{1} \left (x \right )+y_{2} \left (x \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (x \right ) = y_{2} \left (x \right ), y_{2}^{\prime }\left (x \right ) = 6 y_{1} \left (x \right )+y_{2} \left (x \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (x \right ) = y_{1} \left (x \right )+y_{2} \left (x \right ), y_{2}^{\prime }\left (x \right ) = y_{1} \left (x \right )+y_{2} \left (x \right )+{\mathrm e}^{3 x}]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (x \right ) = 3 y_{1} \left (x \right )+x y_{3} \left (x \right ), y_{2}^{\prime }\left (x \right ) = y_{2} \left (x \right )+x^{3} y_{3} \left (x \right ), y_{3}^{\prime }\left (x \right ) = 2 y_{1} \left (x \right ) x -y_{2} \left (x \right )+{\mathrm e}^{x} y_{3} \left (x \right )]
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 2 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = k y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{\prime } \sqrt {1-x^{2} y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x^{4} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{x y-x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (y \cos \left (y\right )-\sin \left (y\right )+x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x}-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = \arctan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \arcsin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-3 x +2\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sin \left (x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|